The Dependence Between Shear Strength Parameters and Microstructure of Subgrade Soil in Seasonal Permafrost Area - Hanbing Liu; Xiang Lyu; Jing Wang; Xin He; Yunlong Zhang (Sustainability, 2020)
Permafrost and seasonal permafrost are widely distributed in China and all over the world. The failure of soil is mainly shear failure, and the strength of soil mainly refers to the shear strength. The two most important parameters of shear strength are cohesion and angle of internal friction. In order to ensure the sustainability of road construction in seasonal permafrost area, the microstructure of subgrade soil was observed and analyzed. First, three subgrade soils with different plasticity indices were prepared for triaxial test and scanning electron microscope (SEM). Then, these specimens underwent freezing–thawing (FT) cycles and were obtained shear strength parameters by triaxial shear test. Next, the microstructure images of soil were obtained by SEM, and the microstructure parameters of soil were extracted by image processing software. Finally, the correlation method was used to analyze the dependence between the shear strength parameters and the microstructure parameters. Results revealed that subgrade soils with a higher plasticity index had higher cohesion and lower angle of internal friction. In addition, with the increase of the number of FT cycles, the diameter and number of soil particles and pores tend to increase, while the roundness, fractal dimension and directional probabilistic entropy of particles decreased. With the increase of the plasticity index, the particle and pore diameter decreased, but the particle and pore number increased. Besides, particle roundness had the greatest influence on the cohesion and angle of internal friction of shear strength parameters.